HOW JADID PRINT CULTURE TURNED REFORM INTO SOCIAL PRACTICE - Dalieva Madina Khabibullaevna (Sciental Journals Publishing, 2026)
This article examines how Jadid reformers in early twentieth-century Turkestan and Bukhara translated cultural critique into concrete social change by means of printed media. I treat “social development” not as an abstract slogan but as a cluster of observable shifts: the spread of functional literacy, the creation of a reading public, the legitimization of new school practices, and the emergence of public argument about knowledge, labor, ethics, and collective responsibility. Drawing on scholarship on Central Asian printing and publishing, I show why Jadidism was structurally tied to print: newspapers and magazines offered a repeatable, distributable format for persuasion, contestation, and agenda-setting under colonial surveillance. Close attention is given to the short but influential life of Taraqqiy (1906) and to later multilingual ventures such as Samarkand and Oyina, as well as to Boḵārā-ye Šarīf in the Bukharan protectorate. The argument is cautious about reach and impact, yet it demonstrates that Jadid publications functioned as a practical “civic technology” that reorganized how reform ideas circulated and became socially actionable.
Keywords: Jadid press, Turkestan, print culture, newspapers, magazines, social development, literacy, public sphere, reform discourse, Bukhara